(untitled) (MAUSAM, 1994)
A IUt ly of PbllWIHI") lt cundury l.nycr (PUll in the lIIunsllun llflllgh !"l’l:illll ha:oo h! ’t’11 Carrl,’t11l1l1 based on MONTDl EX 1989 pilot experiment d ata PilI. structure over land !>hllw’IO lAid l’ , pati,11 lIn,1 tem poral variatums. TIlrCCtypes of PRL- .’IOha lluconvective . monsoon 11111 111) convective boundaryl a yers haw been obv-rved . Ch ar act eri st ic features :I!I:"Ul"i:JI lt wilh Jill"t’relll types of POL have been iJe- l... 1and p rcscnr c..t in th e p:Jlll’r. With the help of observe...1rill ,structure over-eastern. ceutral and wcsrcm M’11m suf llu’ ll1tlll IHn tmullii. ;1111"’1111’1has h«’11 made to develop "PlIl ’(" e ro s e-sec tio ns of PUL UH’r Ind o -G a ngetic plains llu rilli’ act ive. wcuk ,lilt’ bren k monsoon co nd itio n s.